(untitled) (Anclajes, 2021)
The twenty-five volumes of Anclajes call for a reflection on the development of cultural criticism and university publishing in recent decades. A notable group of specialists analyzes the contributions of the journal on topics such as memories and violence, post-humanisms, writings of the self, dissident bodies and subjectivities, revisions of the archive and the canon of imagined languages and cultures.